(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The heat exchanger device usedto transferheat betweenmore than two fluids. The heat exchanger device is used in various industries. This paper captures that optimization of entire annual operating cost. Thus an effort has been made to get a group of optimum dimension of the heat exchanger subjectto given inlet and outlet conditions.Then all the parameters are collected from related industries.The elapsed time and cost to complete the problems are all compared using ABC algorithm, Auction, Spiral,Ant lion, Elephant herding, Bacterial colony, Greedy, Lawler’s, Fireworks and Patterns search for these ten non-traditional methods.In this paper, we have compared the solution to minimize the total cost of shell and tube heat exchanger using ten artificial optimization method. We conclude which method gives a better solution for shell and tube heat exchanger.